An alternative for the conservation, storage, and commercialization of small batch Hop productions - Tommasino, Exequiel Arturo; Ruolo, Maria Soledad; Schenfeld, Esteban Martín (IFRGV - CIAP, INTA, 2024)
A hop conditioning procedure was developed that allows small producers to market it in an economical and practical way, generating a quality product that can be accepted by craft and industrial breweries. This new commercialization format, which we call L100, consists of ground hops and vacuum packaged in "100-gram ingots" and emerges as an alternative to the T-90 pellet. The L100 format aims to enable small producers to store, conserve and market their productions, increase the supply of hops produced in Argentina and offer a product according to the needs of the beer industry.